I got 39 tables.
134+167=301
301/7=43
Total amount of people =344
344/9=38.222 which you would round to 39 tables
Answer:
7
Step-by-step explanation:
5(x-3)=x+13
5x-15=x+13
-x +15
4x=28
divide 28/4
answer is 7
Answer:
The equation of the line passing through the given points is:
![y=-\frac{8}{3}x-11](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B8%7D%7B3%7Dx-11)
Step-by-step explanation:
Given:
The two points are: ![(x_1,y_1)=(-6,5)\textrm{ and }(x_2,y_2)=(-3,-3)](https://tex.z-dn.net/?f=%28x_1%2Cy_1%29%3D%28-6%2C5%29%5Ctextrm%7B%20and%20%7D%28x_2%2Cy_2%29%3D%28-3%2C-3%29)
The equation of a line when two points are given is:
![y-y_1=\left (\frac{y_2-y_1}{x_2-x_1} \right )(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3D%5Cleft%20%28%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%20%5Cright%20%29%28x-x_1%29)
Plug in all the values and simplify.
![y-5=\left (\frac{-3-5}{-3-(-6)} \right )(x-(-6))\\y-5=\left (\frac{-8}{-3+6} \right )(x+6)\\y-5=\left (\frac{-8}{3} \right )(x+6)\\y-5=\frac{-8}{3}x-16\\y=\frac{-8}{3}x-16+5\\\\y=-\frac{8}{3}x-11](https://tex.z-dn.net/?f=y-5%3D%5Cleft%20%28%5Cfrac%7B-3-5%7D%7B-3-%28-6%29%7D%20%5Cright%20%29%28x-%28-6%29%29%5C%5Cy-5%3D%5Cleft%20%28%5Cfrac%7B-8%7D%7B-3%2B6%7D%20%5Cright%20%29%28x%2B6%29%5C%5Cy-5%3D%5Cleft%20%28%5Cfrac%7B-8%7D%7B3%7D%20%5Cright%20%29%28x%2B6%29%5C%5Cy-5%3D%5Cfrac%7B-8%7D%7B3%7Dx-16%5C%5Cy%3D%5Cfrac%7B-8%7D%7B3%7Dx-16%2B5%5C%5C%5C%5Cy%3D-%5Cfrac%7B8%7D%7B3%7Dx-11)
Therefore, the equation of the line passing through the above points is
![y=-\frac{8}{3}x-11](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B8%7D%7B3%7Dx-11)
Answer:
6 is the answer.
Step-by-step explanation:
Using PEMDAS, let's solve.
- (6 - 2 x 2) x 3
- (6 - 4) x 3
- 2 x 3
- 6
Therefore, 6 is the answer.
Hoped this helped.
You have the following expressions given in the problem above:
(y^2/y-3)(y^2-y-6/y^2+y)
By applying the exponents properties, you can simplify it, as it shown below:
(y^2/y-3)(y^2-y-6/y^2+y)
(y^4-y^3-6y^2)/(y^3+y^2-3y2-3y)
(y^4-y^3-6y^2)/(y^3-2y2-3y)
Then, you have:
y^2(y^2-y-6)/y(y^2-2y-3)
(y^2-y-6)/(y^2-2y-3)
The answer is: (y^2-y-6)/(y^2-2y-3)